THE MEANING OF WORK FOR THE ELDERLY IN THE PERSPECTIVE OF SOCIAL CHANGES IN THE EMPLOYMENT MARKET: POLISH DIMENSIONS (Comparative Professional Pedagogy, 2021)
In the 21st century, a time of dynamic civilisational, economic, technological and other changes, the approach to professional work, opportunities of employment as well as personal development and professional career is also changing. The transformation, the dynamic civilisation development, the globalisation and the so-called consumer revolution have significantly influenced the change in views on work and professional career. In this dynamics of transformations, older people, being retired, perceive both the changes and work in a slightly different way than young people entering the labour and employment market. This is due to their inclinations and features characteristic for their age and health condition. Besides, the functioning of seniors in the labour market is not easy in modern times. From the perspective of work in the ‘volatile’ employment market, it can be observed that, on the one hand, the duration of employment is getting shorter and shorter but in this short period of time, within a certain number of working hours, an employee has to ‘deliver’ as much as possible: ideas, initiatives and activities contributing to the development of the employing institution in order not to lose the already short period of employment and the possibility of adding new skills or achievements to the portfolio. Engaging older people in professional work, maintaining their activity in the labour market is possible with properly implemented social, economic, and educational policies with regard to older people. This paper focuses on the essence of work, its value and meaning for older people from the perspective of work activity and retirement experiences. It shows how work has shaped and continues to shape contemporary seniors and how they perceive themselves on the labour market and their own development opportunities.
Keywords: sense of meaning in life; older person; values; work; professional growth; labour market; employment